Effect of TiO2 nanoparticles on the properties of thermoplastic chitosan-based nano-biocomposites obtained by mechanical kneading. (February 2017) - Cano, Laida; Pollet, Eric; Avérous, Luc; Tercjak, Agnieszka
Abstract: Thermoplastic chitosan-based materials were successfully prepared by thermo-mechanical treatment in an internal mixer using volatile (water) and non-volatile (glycerol) plasticizer, and a destructuring agent (acidic solution). TiO2 -based nanoparticles were incorporated at varying contents (1–10 wt%) into the chitosan-based matrix to obtain different nano-biocomposites. The effects of the addition of TiO2 nanoparticles on the properties of the nano-biocomposites, such as crystallinity, thermal stability, morphology and optical, mechanical and surface properties were investigated. The crystallinity of the biopolymer-based matrix decreased as a consequence of the incorporation of TiO2 nanoparticles. The morphological characterization showed a good dispersion of the nanofiller into the polymer matrix and a clear dependence on the TiO2 nanoparticle content. The nano-biocomposites resulted in UV shielding materials as a consequence of the TiO2 incorporation. Moreover, the mechanical properties of the plasticized chitosan were enhanced by the incorporation of TiO2 nanoparticles and were related strongly to the TiO2 nanoparticles content.